Advancing corporate sustainability: a mixed-methods investigation of individual and organizational drivers - Keil, Maike; Rohowsky, Anna; Offermann, Julia; Ziefle, Martina; Arning, Katrin (Frontiers in Sustainability, 2025)
IntroductionAs integral societal actors, companies must engage in corporate sustainability to address climate change and remain competitive. While many factors influencing corporate sustainability have been identified, little research has analyzed them jointly.MethodsTherefore, this study surveyed corporate sustainability leaders in a mixed-methods approach, utilizing semi-structured interviews (N = 25) and an online survey (N = 108) to assess organizational and individual, leader-related drivers.Results and discussionQualitative results highlighted the importance of leadership in sustainability decisions. Quantitative results showed that perceived corporate sustainability correlated with individual factors (e.g., leaders' environmental behavior), while practical sustainability, measured by the Corporate Sustainability Index, was linked to organizational factors (e.g., company size). Hierarchical multiple regression quantified the relative impact of factors and confirmed leaders' environmental citizenship behavior, company size, and annual revenue as key sustainability predictors. The findings provide valuable guidance for organizations and policymakers to support corporate sustainability transformation by empowering sustainability leaders and smaller organizations.